Humanized von Willebrand factor reduces platelet sequestration in ex vivo and in vivo xenotransplant models. (17th October 2021) - Connolly, Margaret R; Kuravi, Kasinath; Burdorf, Lars; Sorrells, Lori; Morrill, Benson; Cimeno, Arielle; Vaught, Todd; Dandro, Amy; Sendil, Selin; Habibabady, Zahra A; Monahan, Jeffery; Li, Tiezheng; et al.
Abstract: The transplantation of organs across species offers the potential to solve the shortage of human organs. While activation of human platelets by human von Willebrand factor (vWF) requires vWF activation by shear stress, contact between human platelets and porcine vWF (pvWF) leads to spontaneous platelet adhesion and activation. This non‐physiologic interaction may contribute to the thrombocytopenia and coagulation pathway dysregulation often associated with xenotransplantation of pig organs in nonhuman primates. Pigs genetically modified to decrease antibody and complement‐dependent rejection (GTKO.hCD46) were engineered to express humanized pvWF (h*pvWF) by replacing a pvWF gene region that encodes the glycoprotein Ib‐binding site with human cDNA orthologs. This modification corrected for non‐physiologic human platelet aggregation on exposure to pig plasma, while preserving in vitro platelet activation by collagen. Organs from pigs with h*pvWF demonstrated reduced platelet sequestration during lung ( p ≤ .01) and liver ( p ≤ .038 within 4 h) perfusion ex vivo with human blood and after pig‐to‐baboon lung transplantation ( p ≤ .007). Residual platelet sequestration and activation were not prevented by the blockade of canonical platelet adhesion pathways. The h*pvWF modification prevents physiologically inappropriate activation of human or baboon platelets by porcine vWF, addressing one cause of the thrombocytopenia and platelet activation observed with xenotransplantation.